Angiogenesis enhanced by treatment damage to hepatocellular carcinoma through the release of GDF15. (31st January 2018) - Dong, Gang; Zheng, Qiong‐Dan; Ma, Min; Wu, Si‐Fan; Zhang, Rui; Yao, Rong‐Rong; Dong, Yin‐Ying; Ma, Hui; Gao, Dong‐Mei; Ye, Sheng‐Long; Cui, Jie‐Feng; Ren, Zheng‐Gang; et al.
Abstract: Transarterial chemoembolization (TACE) is the standard treatment for unresectable hepatocellular carcinoma (HCC). Hypoxia‐induced angiogenesis by TACE is linked to treatment failure; however, whether the chemotherapeutic damage of TACE to HCC could increase tumor angiogenesis has not been explored. The molecular effects of chemotherapy‐damaged HCC cells on the neo‐angiogenesis were investigated in vitro and in vivo. The expression of growth differentiation factor 15 (GDF15) was significantly upregulated in HCC cells exposed to chemotherapeutic agents. GDF15 from chemotherapy‐damaged HCC cells promoted the in vitro proliferation, migration, and tube formation of endothelial cells. The pro‐angiogenic effect of GDF15 was through the activation of Src and its downstream AKT, MAPK, and NF‐κB signaling, which was blocked by thalidomide. The use of thalidomide significantly attenuated the in vivo chemotherapy‐damaged HCC cells‐promoted angiogenesis in nude mice. In conclusion, the chemotherapeutic damage in TACE to HCC could promote tumor angiogenesis via the increased release of GDF15. Thalidomide could reverse these pro‐angiogenic effects. Abstract : Chemotherapeutic damage to hepatocellular carcinoma promotes tumor angiogenesis via the increased release of GDF15. Thalidomide could reverse these pro‐angiogenic effects.